2018
DOI: 10.1002/admi.201800662
|View full text |Cite
|
Sign up to set email alerts
|

Direct Growth of 5 in. Uniform Hexagonal Boron Nitride on Glass for High‐Performance Deep‐Ultraviolet Light‐Emitting Diodes

Abstract: The direct coating of 2D hexagonal boron nitride (h‐BN) on insulating solid glass will endow glass with advanced properties, thus offering killer applications of the new type hybrid of h‐BN glass. However, daunting challenges still remain regarding the direct growth methodology of h‐BN on glass. Herein, a catalyst‐free chemical vapor deposition route for the direct synthesis of 5 in. uniform h‐BN thin films on functional quartz and sapphire glass is developed. The optical transparency, surface wetting, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…[185] Transition metals are among the most common substrates for h-BN synthesis, including Cu, [15,181,[185][186][187] Ni, [183,184,188] Pt, [189] Au, [11] Cu-Ni alloy, [190] etc. Some research groups have also demonstrated direct growth of h-BN on dielectric substrates, [191][192][193][194][195][196][197][198][199] and showed continuous h-BN films without obvious morphology. This is further elaborated in the subsection 'Growth on non-metal substrate'.…”
Section: Chemical Vapor Depositionmentioning
confidence: 99%
See 1 more Smart Citation
“…[185] Transition metals are among the most common substrates for h-BN synthesis, including Cu, [15,181,[185][186][187] Ni, [183,184,188] Pt, [189] Au, [11] Cu-Ni alloy, [190] etc. Some research groups have also demonstrated direct growth of h-BN on dielectric substrates, [191][192][193][194][195][196][197][198][199] and showed continuous h-BN films without obvious morphology. This is further elaborated in the subsection 'Growth on non-metal substrate'.…”
Section: Chemical Vapor Depositionmentioning
confidence: 99%
“…Optical images of h-BN are shown also in[223] e) a quartz substrate and f) a sapphire substrate. Reproduced with permission [199]. Copyright 2018, Wiley-VCH.…”
mentioning
confidence: 99%
“…As the most promising technique, chemical vapor deposition (CVD) was employed to achieve large-area monolayer and few layer h-BN on metal or dielectric substrates by using ammonia borane (NH 3 $BH 3 ) or borazine (B 3 N 3 H 6 ) as the precursor. [14][15][16][17][18][19][20][21][22][23] However, the inhomogeneous thickness, poor crystallinity, toxicity of precursors and complicated procedures limits the application in practical 2D devices. High quality, thickness uniformity, low cost and facile synthesis remain extremely challenging for compound 2D layered materials such as h-BN.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the wet transfer process from metallic surfaces to target substrates would probably degrade the quality of the h-BN and then limit its application in microelectronics. We also noticed that there have been several reports about the direct synthesis of h-BN films on dielectric substrates 21,22 , but the low thickness control and high crystallinity of h-BN films are issues that remain elusive [21][22][23][24] .…”
mentioning
confidence: 97%